Menganalisis Efektifitas Sistem Pengendalian Internal terhadap Pelayanan Publik pada Bidang Perizinan di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Medan - Nisa Sri Rahayu Hsb; Arnida Wahyuni Lubis (LPPM IAI Nasional Laa Roiba Bogor, 2022)
Public services in goverment agencies, especially in the field of licensing services will not be separated from the practice of maladministration. To overcome this practice, a system that can control the implementation of public services is needed, namely the internal control system. The purpose of this research is to analyze the effectiveness internal control system for public services in the field of licensing at the invesment office and one- stop integrated service in the city of Medan. This type of research uses a qualitative description rules and all information obtained from the mechanism of observation, interviews and documentation. The results of this study indicate that the internal control system implemented in DPMPTSP Medan city has not been effective and optimal because there are still many complaints report from the public regarding the procedure system. Which is long- winded, takes a long time in obtaining permits, and it is found that Medan city DPMPTSP officers who work not yet competent and responsible for their work. Keywords: Public Service, Licensing, Internal Control System